Vitamin A deficiency: experience from a tertiary referral UK hospital; not just a low- and middle-income country issue. Issue 18 (12th December 2021) - Marley, Alexandra; Smith, Samuel CL; Ahmed, Ruhina; Nightingale, Peter; Cooper, Sheldon C
Abstract: Objective: Vitamin A (VA) deficiency, more common in low- and middle-income countries (LMIC) secondary to malnutrition, is associated with increased morbidity and mortality. The prevalence and impact of VA deficiency in high-income countries (HIC) where chronic conditions may predispose is less well understood. Design: Interpretation of serum retinol may be affected by inflammation, so C-reactive protein (CRP) levels were sought. Binary logistic regression and generalised estimating equations were performed to review the relationship between CRP and VA. Setting: We examined the scale of low and deficient VA status in our tertiary University Teaching Hospital (HIC). Participants: Patients undergoing serum retinol concentrations 2012–2016 were identified from laboratory records, and records examined. Results: Totally, 628 assays were requested, with eighty-two patients VA low (0·7–0·99 Umol/l) or deficient (<0·7 Umol/l). Sixteen patients were symptomatic (fifteen deficient), predominantly visual. Only one symptomatic patient's VA deficiency was secondary to poor intake. Other symptomatic patients had chronic illnesses resulting in malabsorption. The incidence of a low VA level increases significantly with a raised CRP. Conclusion: The majority of patients tested either were replete or likely to have abnormal VA levels due to concomitant inflammation. A minority of patients had signs and symptoms of VA deficiency and was a cause of significant morbidity, but aetiology differs from LMIC, overwhelmingly malabsorption, most commonly secondary to surgery or hepatobiliary disease. A correlation between inflammation and low VA levels exists, which raises the possibility that requesting a VA level in an asymptomatic patient with active inflammation may be of questionable benefit.